STRATEGI PROMOSI MELALUI MEDIA DIGITAL UNTUK MENINGKATKAN KINERJA PEMASARAN PADA TOKO FELAUSHOP SUMBAWA BESAR - Sucihati, Roos Nana; Londa, Kartini Inesti (Samalewa: Jurnal Riset & Kajian Manajemen, 2024)
This study aims to know the promotional strategies through digital media to improve marketing performance at the Felaushop Store Sumbawa Besar. The type of this study was descriptive used to describe promotional strategies through digital media to improve marketing performance at Felaushop Store Sumbawa Besar. The type of data used was qualitative data obtained directly from research informants using interview techniques. The informants who were sources for this study consisted of owners, employees and customers of the Felaushop Store Sumbawa Besar. Evaluation of marketing performance at the Felaushop Store Sumbawa Besar in this study used the SWOT method. Through SWOT analysis, internal factors (strengths and weaknesses) and external factors (opportunities and threats) can be identified in the marketing of the Felaushop Store Sumbawa Besar. The results of this study showed that the marketing of the Felaushop Store Sumbawa Besar was in quadrant I. The strategy that can be applied in this condition is to support aggressive policies (growth oriented strategy). This can be done using the SO (strength-opportunities) strategy by taking advantage of the strengths and opportunities you have to overcome the weaknesses and threats faced so that you can improve marketing performance at the Felaushop Store Sumbawa Besar. Several strategies that can be implemented in marketing at the Felaushop Store Sumbawa Besar, namely: 1). Presenting various creative, innovative and different products from competitors, 2). Providing maximum service, 3). Offering prices that are relatively cheaper than competitors, 4). Carrying out various marketing events, and 5). Optimizing promotions through digital media.